EMPOWERING JUNIOR HIGH SCHOOL STUDENTS' EMPATHY AND COLLABORATION WITH DESIGN THINKING AND PJBL - Istikomayanti, Yuswa; Mitasari, Zuni; Trianawati, Anis; Anggraeni, Pratika Desy (LPPM IKIP PGRI Pontianak, 2023)
This research seeks to guide the empathy of junior high school students through combining design thinking with PjBL (Project Based Learning) as many as 83 students, and two science teachers participated in this research. Data collection was carried out through interviews, observation notes, reflection notes, and student assessment rubrics to collect qualitative data. Aspects of student empathy and collaboration are built into the learning of digestive system material. Empathy as an initiator in project-based learning includes aspects of self-integrity and empathy for others which are closely related to elements of collaboration including aspects of cooperation, ways of communicating, positive dependence and social coordination. Design thinking as a process thinking framework includes the empathization stage, problem formulation, constructing ideas, constructing prototypes, and tests as student learning stages. Contextual learning with design thinking and PjBL is expected to be an integrated model to achieve aspects of the Pancasila student profile and 21st century skills.